Odpowiedzi

2010-02-12T14:26:52+01:00
A.2x-6y; x=-2 y=1 2*(-2)-6*1=4-6=(-2)
b.3x-4y+5; x=1 y=3 3*1-4*3+5=3-12+5=(-9)+5=(-4)
c.4x=y-7; x=-1 y=0 niewiem
d.2y-8+3x; x=-2 y=6 2*(-2)-8+3*6=4-8+18=14
  • Użytkownik Zadane
2010-02-12T14:33:45+01:00
A)2x-6y; x=-2 y=1
2*(-2)-6*1
-4-6=-10
b)3x-4y+5; x=1 y=3
3*1-4*3+5
3-12+5=-4
c)4x=y-7; x=-1 y=0
4*(-1)=0-7
-4=-7
d)2y-8+3x; x=-2 y=6
2*6-8+3*(-2)
12-8-6
4-6=-2
Proszę.
2010-02-12T14:41:27+01:00
A.2x-6y; x=-2 y=1
2*(-2)-6*1 = -4-6 = -10

b.3x-4y+5; x=1 y=3
3*1-4*3+5 = 3-12+5 = -4

c.4x+y-7; x=-1 y=0
4*(-1)+0-7 = -4+0-7 = -11

d.2y-8+3x; x=-2 y=6
2*6-8+3*(-2) = 12-8+(-6) = -2